Alarm sings for primary immunodeficiency diagnosis. A proposal adapted to the Cienfuegos province - Yosvany Castillo Leyva; Alain Alonso Remedios; Grace de Lara García; Daynelis Pardo Martínez; Albert Vera Razumova (Medisur)
Foundation: immunodeficiency diseases are a heterogeneous group of disorders that reflect one or more components of the immune system quantitative and / or qualitative deficit. The fast reference of these cases to the immunology consultation decreases morbidity and mortality. Objective: to establish the alarm signs for a primary immunodeficiency diagnosis, that will be a referral criterion in the province of Cienfuegos. Methods: eleven articles on alarm signs for primary immunodeficiencies diagnosis, published by associations and international organizations dedicated to immunology were reviewed. The sign diagnostic value was determined as a criterion for inclusion in the disease warning signs list. Results: Fifteen alarm signs were established based on their reporting frequency and / or assigned diagnostic value. Conclusion: alarm signs established by the Cienfuegos provincial immunology group will be taken as referral criteria for immunology consultation due to primary immunodeficiency suspicion, which may contribute to decrease its morbidity.